2003
DOI: 10.4049/jimmunol.171.8.4406
|View full text |Cite
|
Sign up to set email alerts
|

IL-8/CXCL8 and Growth-Related Oncogene α/CXCL1 Induce Chondrocyte Hypertrophic Differentiation

Abstract: Foci of chondrocyte hypertrophy that commonly develop in osteoarthritic (OA) cartilage can promote dysregulated matrix repair and pathologic calcification in OA. The closely related chemokines IL-8/CXCL8 and growth-related oncogene α (GROα)/CXCL1 and their receptors are up-regulated in OA cartilage chondrocytes. Because these chemokines regulate leukocyte activation through p38 mitogen-activated protein kinase signaling, a pathway implicated in chondrocyte hypertrophic differentiation, we tested whether IL-8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
151
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 68 publications
(102 reference statements)
4
151
0
3
Order By: Relevance
“…IL-8 and ENA-78 are potent inducers of angiogenesis (32), which is a marked feature in our arthritis model (9,10). IL-8 also contributes to the pathologic changes observed in arthritis through p38 MAPK pathway activation (33), which can lead to hypertrophic differentiation, alteration in collagen subtype expression, and cartilage calcification. PBEF was also up-regulated, and this cytokine perpetuates inflammation since it stimulates IL-6 and IL-8 expression (34).…”
Section: Discussionmentioning
confidence: 80%
“…IL-8 and ENA-78 are potent inducers of angiogenesis (32), which is a marked feature in our arthritis model (9,10). IL-8 also contributes to the pathologic changes observed in arthritis through p38 MAPK pathway activation (33), which can lead to hypertrophic differentiation, alteration in collagen subtype expression, and cartilage calcification. PBEF was also up-regulated, and this cytokine perpetuates inflammation since it stimulates IL-6 and IL-8 expression (34).…”
Section: Discussionmentioning
confidence: 80%
“…The rise in TG activity in guinea pig OA chondrocytes holds further significance because of the major role of TG activity in promoting both cytokine-induced matrix calcification and chondrocyte hypertrophic differentiation, which results in a dysregulated matrix-reparative response in OA (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Merz et al showed that IL-8 expression is associated with chondrocyte hypertrophy in OA, which possibly promotes nonphysiological calcification and matrix repair processes [23]. Matsukawa et al was able to show that IL-8 induces destruction of cartilage [24].…”
Section: Discussionmentioning
confidence: 99%